Exchanging Expertise across Cultures and Time: Participatory Design Approaches for Creating Community Museums. (2nd September 2020) - Taffe, Simone; Kelly, Meghan
Abstract: This paper presents a case study where participatory design practices were used to design a cultural museum and inaugural exhibition with designers from an Australian university and the Kelabit community in the Highlands of Borneo. We draw on experiences from fieldtrips, across a five-year period, investigating the exchange of expertise between participants. The findings show a shift in roles when sharing expertise throughout our participatory design process. Participants experienced a lack of clarity and a sense of discomfort while participating in the design of the museum resulting in the need to continually negotiate leadership of the project. The designers discovered their role was to facilitate intangible conversations into tangible outcomes, where participatory design tools reshaped conversations rather than designed final artefacts. We argue that when exchanging expertise across cultures in participatory design, participant roles become organic and ambiguous.